A protein-leucine supplement increases branched-chain amino acid and nitrogen turnover but not performance. - Nelson, A. R.; Phillips, S. M.; Stellingwerff, T.; Rezzi, S.; Bruce, J.; Breton, I.; Thorimbert, A.; Guy, P. A.; Clarke, J.; Broadbent, S.; Rowlands, D. S. (Medicine & Science in Sports & Exercise, 2012)
Purpose: This study aimed to determine the effect of postexercise protein-leucine coingestion with CHO-lipid on subsequent high-intensity endurance performance and to investigate candidate mechanisms using stable isotope methods and metabolomics.